Controlled Synthesis of "Reverse Pluronic"‐Type Block Copolyethers with High Molar Masses for the Preparation of Hydrogels with Improved Mechanical Properties. Issue 3 (9th January 2020) - Markus, Felix; Bruckner, Johanna R.; Naumann, Stefan
Abstract: Hydrogels based on Pluronics (EOn/2 ‐POm ‐EOn/2, EO = ethylene oxide, PO = propylene oxide) have been frequently investigated, yet key limitations still remain, including a propensity for quick erosion and insufficient mechanical robustness. This issue can be alleviated by creating "reverse Pluronics" (PO n /2 ‐EO m ‐PO n /2 ), which is proposed to enable the formation of physical cross‐links via a micellar network. Until recently, however, efforts in this direction were aggravated by synthetic difficulties, specifically prohibiting the realization of poly(propylene oxide) (PPO)‐moieties with a high DP. In this study, an organocatalytic polymerization method is employed to synthesize "reverse Pluronics, " resulting in highly defined polymers ( Ð M ≤ 1.02–1.07, M n up to 35 000 g mol −1 ) with exceptionally long PPO blocks. The higher molar mass and the reverse constitution of the polyether combine to enable the generation of thermoresponsive hydrogels with a storage modulus that is increased tenfold relative to reference samples. Gelation temperature and maximum storage modulus ( G ′max ) are readily influenced by the choice of the polyether (down to 5 wt%). The improved mechanical properties are accompanied by an increased resistance toward erosion in water. Isotactic enrichment is presented as an additional tuning parameter for hydrogel properties. Abstract : Amphiphilic triblock copolyethers of the type PO n /2 ‐EO m ‐PO n /2 (EO = ethylene oxide, PO = propylene oxide) are synthesized in a well‐controlled, metal‐free manner ( Ð M = 1.02–1.07) and applied for the formation of thermoresponsive hydrogels. The "reverse" block placement in these Pluronics directly impacts the gelation mechanism and entails significantly improved mechanical robustness, addressing a long‐standing issue for polyether‐derived hydrogels.